Clinical charactistics of abnormal thyroid function in patients with maintenance hemodialysis - WANG Hong-na; ZHANG Yue-feng (Linchuang shenzangbing zazhi)
Objective To investigate the abnormal thyroid functions and influencing factors in patients with maintenance hemodialysis(MHD).Methods Sixty-nine patients with MHD were selected,and free tri-iodothyronen(FT3),free thyronine(FT4)and thyroid-stimulating hormone(TSH)were determined.Thyroid disorders were classified into pure low FT3,low FT3 and low FT4,subclinical state groups.The clinical biochemical results were compared among different groups.Results The proportion of the thyroid dysfunction in patients with MHD was 58%.There were more patients,who were older than 60 years,in pure low FT3 group than in normal control group(P<0.05).The difference was statistically significant in red cells,hemoglobin,HCT,calcium-phosphorus pruduct and Alb between low FT3 and Low FT4 group and normal control group(P<0.05).There was also significant difference in red cells and cholesterol between subclinical state group and normal control group(P<0.05).However,there was no significant difference in cardiac structure and pulmonary hypertention between thyroid dysfunction groups and normal control group.Conclusions Clinicians should pay more attention to the thyroid dysfunction,which may influence the prognosis of patients with MHD.